(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The integration of Virtual Reality (VR) into journalism has revolutionized the way news is produced, presented, and perceived. This article explores the transformative potential of VR in reshaping journalistic practices by offering immersive storytelling, fostering empathy, and redefining audience engagement. It investigates the pedagogical implications for journalism education, the ethical challenges inherent in immersive content creation, and the socio-cultural impact of this emerging technology. By examining international case studies and current practices, the article highlights how VR is not only a technological innovation but also a catalyst for redefining the role of journalists in the digital age. It concludes by addressing the future directions of VR journalism and its capacity to create more profound connections between stories and their audiences.